Increasing the Digital Literacy among Tourism Awareness Groups for Sustainable Tourism Village Development - Nurhayati Darubekti; Sri Handayani Hanum; Patricia Ekowati Suryaningsih; Deli Waryenti (MITRA: Jurnal Pemberdayaan Masyarakat, 2022)
Given the effects of digital transformation on the tourism industry, the trends and paradigms in tourism have changed considerably, necessitating some creativity in the management of tourist villages as tourist destinations. The knowledge about the digitalization of tourism can in fact, help promote popular travelling sites, with both patrons and business owners benefitting from better systems of communication, reservation, and guest service. However, the institutional operations and management of the tourism awareness group (pokdarwis) in the community have yet to be optimally effective due to some institutional and managerial issues. Some 21st-century digital skills are identified to be helpful for this pokdarwis in its management of tourist villages, namely technical knowledge, information, communication, collaboration, creativity, and implementation of the Electronic Information and Transaction (ITE) Law. To support this effort, this community service activity (PKM) was carried out for 27 participants, who were all pokdarwis administrators, from May to October 2022, using a CBT approach. The results of the PKM activity indicate an increasing understanding that the ITE Law can provide a broad legal framework for online activities. There is also increasing awareness of social media as a communication medium that can facilitate online communication, exchange, and information access for the public, regardless of time or location. Of many social media platforms, YouTube and Instagram have become the options for publishing tourism information in Surau Village. It is nonetheless agreed that social media should be used with caution to avoid accusations of spreading false information and to ensure an effective implementation of the promotion activities. Considering this, mentoring in the use of social media in the marketing efforts will still be provided in the form of consultation, learning, and counseling.